2019
DOI: 10.1515/arh-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymer–Surfactant Complexes as Flow Enhancers: Characterization and Performance Evaluation

Abstract: Artificial polymeric additives are known, and experimentally proven, to be effective drag reducing agents in pipelines with turbulent flow medium. The artificial nature of these additives and their low resistance to high shear forces, exerted by the pipeline geometries and equipment, are considered as major problems against a wider implementation in other industrial applications. The present work introduces a new polymer-surfactant complex of two organic additives (chitosan and sodium laurel ether sulfate, SLE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…This will create a bonding environment where the presence of the surfactant's molecules on the polymers network surface will enable the bonding of nearby polymeric molecules as well, resulting in larger macroaggregates that act as one unit with higher resistance to mechanical degradation. Mahmood et al [17] created a polymer-surfactant complex using chitosan polymer and sodium laurel ether sulfate surfactant and used it as a DRA in a water flow system. They found that the drag reduction performance of the proposed complex has a higher resistance to mechanical degradation and higher drag reduction performance compared to the performances of the individual additives.…”
Section: Introductionmentioning
confidence: 99%
“…This will create a bonding environment where the presence of the surfactant's molecules on the polymers network surface will enable the bonding of nearby polymeric molecules as well, resulting in larger macroaggregates that act as one unit with higher resistance to mechanical degradation. Mahmood et al [17] created a polymer-surfactant complex using chitosan polymer and sodium laurel ether sulfate surfactant and used it as a DRA in a water flow system. They found that the drag reduction performance of the proposed complex has a higher resistance to mechanical degradation and higher drag reduction performance compared to the performances of the individual additives.…”
Section: Introductionmentioning
confidence: 99%